Analysis Of Factors Affecting Auditor Performance At The Public Accounting Office Of Medan City - Fani Adelia; Shita Tiara (Institute of Computer Science (IOCS), 2022)
Abstract This study aims to determine the effect of work experience, gender, job satisfaction, work discipline, independence and audit fees on the performance of auditors at the Medan City Public Accounting Firm. The results of the multiple linear regression test obtained the equation Y = -15.856 + (-0.386)X1 + 0.041X2 + 0.646X3 + 0.413X4 + 0.482X5 + 0.539X6 + e, where only the variables of job satisfaction, work discipline, independence and audit fees have significant effect on the auditor performance variable, while the work experience and gender variables do not have a significant effect on the auditor performance variable. To determine whether or not the hypothesis is accepted in this study, the t test (partial) and the F test (simultaneous) are used. For the results of the t-test (partial) on the work experience variable, the value of tcount > ttable is -1.447 < 2.03, on the gender variable, the value of tcount > ttable is 0.066 < 2.03, on the job satisfaction variable, the value of tcount is obtained > ttable which is 2.184 > 2.03, on the work discipline variable, the value of tcount > ttable is 2.259 > 2.03, on the independence variable, the value of tcount > ttable is 3.044 > 2.03, and on the audit fee variable, the value is obtained tcount > ttable that is 2,589 > 2.03. Thus, H1 and H2 were rejected because tcount < ttable, while H3, H4, H5 and H6 were accepted because tcount > ttable. Then for the results of the F test (simultaneous) the value of Fcount > Ftable is 18.114 > 2.86. Thus H7 is accepted because Fcount > Ftable. Therefore, it can be concluded that only job satisfaction, work discipline, independence and audit fees partially have a significant and positive effect on the performance of auditors at the Medan City Public Accounting Firm. While work experience and gender partially have no significant and negative effect on the performance of auditors at the Medan City Public Accounting Firm. But all independent variables, namely work experience, gender, job satisfaction, work discipline, independence and audit fees simultaneously have a significant and positive effect on the performance of auditors at the Medan City Public Accounting Firm.